2020
DOI: 10.3389/fonc.2020.01658
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Tumor Cells Expressing the Prostate Specific Membrane Antigen (PSMA) Indicate Worse Outcome in Primary, Non-Metastatic Triple-Negative Breast Cancer

Abstract: Background: We analyzed mRNA profiles of prostate cancer related genes in circulating tumor cells (CTCs) of primary, non-metastatic triple-negative breast cancer (TNBC) patients (pts) before and after neoadjuvant chemotherapy to elucidate the potential of prostate cancer targets in this BC subgroup. Method: Blood from 41 TNBC pts (n = 41 before / 26 after therapy) was analyzed for CTCs applying the AdnaTest EMT-2/Stem Cell Select. Multimarker RT-qPCR allowed the detection of the prostate specific antigen PSA, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 74 publications
0
12
0
1
Order By: Relevance
“…7b–i ). The correlation between PSMA overexpression and early relapse of BC was also observed in CTCs 48 . To validate the performance of the EV P signature in the prognostic prediction of PFS, we further collected 16 plasma samples from MBC patients prior to treatment.…”
Section: Resultsmentioning
confidence: 68%
“…7b–i ). The correlation between PSMA overexpression and early relapse of BC was also observed in CTCs 48 . To validate the performance of the EV P signature in the prognostic prediction of PFS, we further collected 16 plasma samples from MBC patients prior to treatment.…”
Section: Resultsmentioning
confidence: 68%
“…Patients with PSMA-positive CTCs before undergoing chemotherapy were less likely to achieve pathological complete remission after chemotherapy. Recurrence occurred earlier if PSMA expression was detected (p = 0.0039) and overall survival rates were lower (p = 0.0059) 42 . Evaluation of the PSMA status of CTCs could help to predict the response to PSMA-targeted therapy in triple-negative breast cancer.…”
Section: Other Alternatives To Psma Diagnosismentioning
confidence: 99%
“…Die Patientinnen, die vor dem Erhalt einer Chemotherapie PSMA-positive CTCs hatten, erreichten nach jener Therapie weniger häufig pathologische Komplettremissionen. Bei einer Expression des PSMAs kam es früher zu einem Rezidiv (p = 00 039) und zu einem geringeren Gesamtüberleben (p = 0,0059) 42 . Gegebenenfalls könnte eine Evaluation des PSMA-Status auf CTCs das Ansprechen einer PSMA-gerichteten Therapie beim triple-negativen Mammakarzinom vorhersagen.…”
Section: Weitere Alternativen Zur Psma-diagnostikunclassified
“…However, clinical samples of breast cancer can express both fulllength AR and AR-V7 (13)(14)(15)(16). Recently it was shown that expression of AR-V7 measured in circulating tumor cells of patients with metastatic breast cancer was associated with bone metastases and also failure of TNBC to therapies (13,52). Thus, application of AR-NTD inhibitors such as EPI-7170 that inhibit the transcriptional activities of both AR-V7 and full-length AR (23,25,26) may be beneficial for the treatment of TNBC as well as CRPC.…”
Section: Discussionmentioning
confidence: 99%